2007
DOI: 10.1080/13607860600735812
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and depression in older people: Evidence from underprivileged refugee and non-refugee communities in Lebanon

Abstract: Religiosity is an important aspect of the life of older people, particularly in the Arab region where religiosity is an important part of daily social and political life. Studies have documented the relationship between religiosity and depression among older people, but none in the region. A total of 740 persons aged 60 + were interviewed in three poor urban areas of Lebanon, one of which was a Palestinian refugee camp. The questionnaire included five items on religiosity covering organizational and intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…Soonthornchaiya and Dancy (2006) found that adherence to Buddhism and to Buddhist teachings of acceptance of change helped older Thai immigrants cope with depression. Several studies have also established the positive health effects associated with religious activities among older Taiwanese, Japanese, and Palestinians (Chaaya et al 2007;Hahn et al 2004;Krause et al 1999;Yeager et al 2006).…”
Section: Factors Affecting Health Of Older Immigrants and Refugeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soonthornchaiya and Dancy (2006) found that adherence to Buddhism and to Buddhist teachings of acceptance of change helped older Thai immigrants cope with depression. Several studies have also established the positive health effects associated with religious activities among older Taiwanese, Japanese, and Palestinians (Chaaya et al 2007;Hahn et al 2004;Krause et al 1999;Yeager et al 2006).…”
Section: Factors Affecting Health Of Older Immigrants and Refugeesmentioning
confidence: 99%
“…Living in a co-ethnic community provided the refugees with much-needed social support and buffered pressures to assimilate into the host nation (Esses et al 2001;Reitz and Sklar 1997). Further the refugees could bond and share their experiences with others with the same beliefs and values (Chaaya et al 2007;Litwin 2006).…”
Section: Mesosystemmentioning
confidence: 99%
“…As confirmed by Chaaya, Sibai, Fayad, and El-Roueiheb (2007), religiosity is an important aspect in the life of the elderly in Arab countries in general. It is an important element in daily social and political life.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies in Lebanon have focused on nursing home populations Doumit & Nasser, 2010), on older persons living in refugee camps and 'vulnerable' communities (Chaaya, Sibai, Fayad, & El-Roueiheb, 2007;Saab, El-Roueiheb, Chaaya, & Sibai, 2005) or on policy and macro analyses (Chemali, Hospers et al, 2007;Sibai et al, 2004). Some examine particular aspects of older peoples' lives and health arising as data subsets of larger general population studies, primarily smoking, cardiovascular disease, nutrition, mortality rates, and residence patterns (Chaaya, Mehio-Sibai, & El-Chemaly, 2006;MOSA, 2009;Sibai, Beydoun, & Tohme, 2009;Sibai, Kanaan, Chaaya, & Campbell, 2007;Sibai, Yount, & Fletcher, 2007).…”
Section: Introductionmentioning
confidence: 99%